Erratum: Systematics and biogeography of Tropical Eastern Pacific Chthamalus with descriptions of two new species (Cirripedia, Thoracica). Zootaxa 1574: 1–30 (2007) - Pitombo, Fabio Bettini; Burton, Ron (Zootaxa, 2018)
We report a lapsus calami in our explanation of the etymology of the name Chthamalus southwardorum sp. nov. in Pitombo & Burton 2007.